Retention of a Swallowed Dental Tool in the Small Bowel: Unusual Lodgment and Prolonged Conservative Management - Ken Chapman Kigozi; Nevis Agirembabazi; Andrew Marvin Kanyike; Racheal Nalunkuma; Rachael Mukisa Nakandi; Simon Peter Nsingo; Robinson Ssebuufu (Case Reports in Dentistry)
Accidental ingestion of foreign bodies during dental procedures is relatively common, with the potential for serious complications, including intestinal perforations and severe pulmonary disorders. Our case report describes the prolonged, asymptomatic retention of a swallowed hex driver in the small bowel of a 38-year-old male, managed conservatively over an extended period. The patient, with a significant medical history of depression, was undergoing a dental procedure involving implant-supported restorations when the incident occurred. Initial x-rays confirmed the presence of the hex driver in the gastrointestinal tract. Despite its stationary position for over a week, it passed naturally without requiring invasive intervention. This case highlights the importance of individualized patient care and deferring recommendations for intervention in certain instances. We recommend a more individualized approach to managing ingested foreign bodies in dental settings, emphasizing the need for tailored strategies based on the patient’s specific circumstances and clinical stability.